Awareness Regarding Obesity and Healthy Lifestyle Practices among College Students in Mandya - Mythily MR; Vinay M; Harish BR (National Journal of Community Medicine, 2018)
Introduction: Non communicable diseases are important among the adult population in developed and developing countries. Overweight & obesity are important risk factors for development of these NCDs. Healthy lifestyle measures when followed proper- ly help in the prevention & control of disease and the risk factors causing it. Awareness about the disease & healthy lifestyle practic- es is the first step in prevention and management of NCDs. This study was taken up to assess the awareness about obesity and healthy lifestyle practices among college students in Mandya. Methods: This cross-sectional study was conducted in October 2016 to November 2016 among 321 Bachelor of Commerce stu- dents in Mandya, by interview method using a semi-structured, pre-tested questionnaire. Results: The study revealed that 205 (63.9%) knew the difference between obesity and overweight. 52 (16.2%) knew about the use of Body Mass Index for diagnosis of obesity. All the study partici- pants had heard about healthy lifestyle. 260 (81.0%) knew that healthy lifestyle includes balanced diet & regular physical activity. Conclusion: Awareness regarding obesity was poor. While the students knew about some healthy lifestyle practices, their know- ledge on the whole was inadequate.